Financial Analysis of Beef Cattle Business in People's Farms of Pulau Rakyat District Asahan Regency - krisni handayani; I. Sembiring; G. A. W. Siregar (Jurnal Peternakan Integratif, 2020)
Beef cattle are raised with the main purpose of producing meat. This study aims to determine the financial aspects of breeders on raising beef cattle and whether raising beef cattle can help the financial of breeders. The research was conducted in Pulau Rakyat subdistrict, Asahan Regency from July until August 2020. The types of data used were primary data and secondary data. Determination of the sample by stratified sampling, namely by dividing three groups based on beef cattle population, namely the low population group (1-10 cattle), the medium population group (11-20 cattle) and the high population group (21-41 cattle), then by purposive sampling, namely took 9 farmers from each population group. The data analysis method used financial analysis. Parameters were R/C, BEP, Net B/C, Gross B/C, NPV, IRR and PP The results showed that the breeders' acceptance could meet the production costs so that the income was positive or profitable. Financial analysis of beef cattle raising were obtained R/C value >1, BEP value >0, Net B/C value and Gross B/C >1, NPV value >0 or positive value, IRR value were 25.85%, 25.80% and 26% which were higer than interest rate of 16.75% respectively. The PP value was 7, 7 and 5 months respectively before the project age (5 years).